Sex differences in thermoregulation in mammals: Implications for energy homeostasis - Fernández-Peña, Carlos; Reimúndez, Alfonso; Viana, Félix; Arce, Victor M.; Señarís, Rosa (Frontiers in Endocrinology, 2023)
Thermal homeostasis is a fundamental process in mammals, which allows the maintenance of a constant internal body temperature to ensure an efficient function of cells despite changes in ambient temperature. Increasing evidence has revealed the great impact of thermoregulation on energy homeostasis. Homeothermy requires a fine regulation of food intake, heat production, conservation and dissipation and energy expenditure. A great interest on this field of research has re-emerged following the discovery of thermogenic brown adipose tissue and browning of white fat in adult humans, with a potential clinical relevance on obesity and metabolic comorbidities. However, most of our knowledge comes from male animal models or men, which introduces unwanted biases on the findings. In this review, we discuss how differences in sex-dependent characteristics (anthropometry, body composition, hormonal regulation, and other sexual factors) influence numerous aspects of thermal regulation, which impact on energy homeostasis. Individuals of both sexes should be used in the experimental paradigms, considering the ovarian cycles and sexual hormonal regulation as influential factors in these studies. Only by collecting data in both sexes on molecular, functional, and clinical aspects, we will be able to establish in a rigorous way the real impact of thermoregulation on energy homeostasis, opening new avenues in the understanding and treatment of obesity and metabolic associated diseases.